Analisis Perhitungan Pajak Bumi dan Bangunan Berbasis Data 3D Menggunakan UAV dan LiDAR di Kecamatan Baso, Kabupaten Agam - Zikra, Afdhal; Yulfa, Arie (Lembaga Yasin AlSys, 2025)
Land and Building Tax (PBB) calculations using conventional methods often face obstacles in terms of accuracy and efficiency. This research implements UAV (Unmanned Aerial Vehicle) technology integrated with LiDAR sensors to optimize PBB calculations in Baso District, Agam Regency in 2024. The research method used is applied research with a quantitative approach, using DJI Terra and TerraSolid software for data acquisition and processing. The results showed that UAV-LiDAR technology is able to produce 3D spatial data that presents detailed information about the dimensions of tax objects, including area, volume, and height of buildings. Compared to conventional 2D methods, this technology shows significant advantages in assessing multi-storey buildings and complex structures. The resulting point cloud data supports precise object classification and more accountable tax assessment. Although its implementation requires high initial investment, the technology proves effective in improving the validity of tax object data and strengthening the PBB calculation base. This research contributes to the modernization of local taxation system through the utilization of the latest geospatial technology.